Two Novel HSD17B4 Heterozygous Mutations in Association With D-Bifunctional Protein Deficiency: A Case Report and Literature Review - Chen, Si; Du, Linrun; Lei, Yihui; Lin, Yuanyuan; Chen, Shangqin; Liu, Yanli (Frontiers in Pediatrics, 2021)
Background: D-bifunctional protein deficiency (D-BPD) is an autosomal recessive disorder caused by peroxisomal β-oxidation defects. According to the different activity of 2-enoyl-CoA hydratase and 3-hydroxyacyl-CoA dehydrogenase protein units, D-bifunctional protein defects can be divided into four types. The typical symptoms includes hypotonia and seizures. The gene that encodes D-BP was HSD17B4, which is located on chromosome 5q23.1. Case presentation: We report the first case of D-BPD in a Chinese patient with neonatal onset. Cosmetic malformations, severe hypotonia, seizures, and cosmetic deformities are prominent. The blood bile acid profile showed increased taurocholic acid, glycocholic acid and taurochenodeoxycholic acid. very long-chain fatty acids (VLCFA) revealed significant increases in hexacosanoic acid (C26:0), tetracosanoic acid/docosanoic acid (C24:0/C22:0), and hexacosanoic acid/docosanoic acid (C26:0/C22:0). Cranial MRI revealed bilateral hemispheric and callosal dysplasia, with schizencephaly in the right hemisphere. EEG showed loss of sleep-wake cycle and epileptiform discharge. Other examinations including abnormal brainstem auditory evoked potentials(BAEP) and temporal pigmented spots on the optic disc in the right eye. After analysis by whole exome sequencing, a heterozygous c.972 + 1G > T in the paternal allele and c.727T > A (p.W243R) in the maternal allele was discovered. He was treated with respiratory support, formula nasogastric feeding, and antiepileptic therapy during hospitalization, and died at home due to food refusal and respiratory failure at the age of 5 months. Conclusions: Whole-exome sequencing should be performed in time to confirm the diagnosis when the newborn presents hypotonia, seizures, and associated cosmetic malformations. There is still a lack of effective radical treatment. Supportive care is the main treatment, aiming at controlling symptoms of central nervous system like seizures, and improving nutrition and growth. The disease has a poor outcoming, and infants often die of respiratory failure within 2 years of age. In addition, heterozygous deletion variant c. 972 + 1G > T and missense mutations c. 727T > A (p.W243R) are newly discovered pathogenic variants, which deserves further study.